The Alliance in a Friendship Coaching Intervention for Parents of Children With ADHD - Lerner, Matthew D. (2011)
The alliance between parent and therapist was observed in a group-based parent-training intervention to improve social competency among children with attention-deficit/hyperactivity disorder (ADHD). The intervention, called Parental Friendship Coaching (PFC), was delivered to 32 parents in small groups as part of a randomized clinical trial. PFC was delivered in eight, 90-minute sessions to parents; there was no child treatment component. Observed parent–therapist alliance recorded among 27 of the parents was measured using the Therapy Process Observational Coding System—Alliance scale (TPOCS-A; McLeod, 2005). Early alliance and change in alliance over time predicted improvements in several parenting behaviors and child outcomes, including peer sociometrics in a lab-based playgroup. These preliminary findings lend support to the importance of examining the parent–therapist alliance in parent-training groups for youth social and behavioral problems.